2017
DOI: 10.1080/20008198.2017.1309934
|View full text |Cite
|
Sign up to set email alerts
|

Ever at the ready for events that never happen

Abstract: Stress, whether daily stress, work stress or traumatic stress, is unhealthy. This lecture covers three recent theoretical approaches in explaining the mechanisms underlying the influence of psychological stress on somatic health. It is argued that stress research should focus less on stressors themselves and put more emphasis on prolonged stress responses. Three mechanisms are identified that cause this unhealthy prolonged stress response: first, the partly-proven mechanism of perseverative cognition; second, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 115 publications
(119 reference statements)
0
26
0
Order By: Relevance
“…It is possible that different types of interventions will be needed if the negative effects of perseverative cognition differ across contexts. If, for instance, the negative effects are stronger during social interaction, interventions need to change the ways in which people are thinking and communicating during communication episodes to reduce maladaptive cognition and biased processing (Brosschot, 2017;S. Cacioppo et al, 2015;Kok & Fredrickson, 2014;Smallwood & Schooler, 2006).…”
Section: Are These Associations Moderated By Social Context?mentioning
confidence: 99%
See 3 more Smart Citations
“…It is possible that different types of interventions will be needed if the negative effects of perseverative cognition differ across contexts. If, for instance, the negative effects are stronger during social interaction, interventions need to change the ways in which people are thinking and communicating during communication episodes to reduce maladaptive cognition and biased processing (Brosschot, 2017;S. Cacioppo et al, 2015;Kok & Fredrickson, 2014;Smallwood & Schooler, 2006).…”
Section: Are These Associations Moderated By Social Context?mentioning
confidence: 99%
“…Research clearly demonstrates that frequent rumination and worry are harmful to health and well‐being (Brosschot, ). Yet, questions remain about the specific ways in which people experience rumination and worry in the context of their everyday lives (Kircanski, Thompson, Sorenson, Sherdell, & Gotlib, ; Ottaviani, Medea, Lonigro, Tarvainen, & Couyoumdjian, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An elevated sense of current threat and reduced sense of safety are fundamental in Ehlers and Clark's cognitive model of post-traumatic stress disorder (PTSD) and thought to arise as early symptoms in the disorder, later accompanied by re-experiencing, avoidance and hyperarousal (Ehlers & Clark, 2000). It has also been suggested that perceived safety may be the essential component in turning a chronic stress response off (Brosschot, 2017). In this theory, the stress response seen in an individual with PTSD could be viewed as the 'default response' in the individual whenever and for as long as there is an absence of perceived safety.…”
Section: Introductionmentioning
confidence: 99%